IMPLEMENTASI PENILAIAN OTENTIK BIDANG STUDI PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI DI SMAN 1 DEMPET JAWA TENGAH - Hadi Nurrohim (Universitas Muhammadiyah Metro, 2017)
Authentic assessment is a variant of assessment in the Curriculum 2013. Authentic assessment needs to be implemented well in every field of study, so that learners can get maximum results. Public senior high school 1 Dempet is one of the schools that has implemented the Curriculum 2013, as well as its authenticassessment which is special in the field of study of Islamic Education and Character. This authentic assessment can be successful if the teacher follows the procedures and steps. So also with the teachers of Islamic education in Public senior high school 1 Dempet, who with all the shortcomings and advantages apply authentic assessment. This study aims to identify and explain the process of choosing a strategy and establishing an approach in the authentic assessment of the field of Islamic education and Character Public senior high school 1 Dempet study. Then he explains and explains the strategies and approaches in the authentic assessment of Islamic education and Character Public senior high school 1 Dempet study areas. Two things are worth to investigate, given that there are still teachers who have not really understand and apply authentic assessment. Through this research, it is generated that Islamic education teachers have applied authentic assessments well, so that it can provide a positive for the learners.